Geology - Genesis of Titaniferous Magnetites and Associated Rocks of the Lake Sanford District, New York - J. L. Gillson (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1957)
THE big mass of anorthosite in the Lake Sanford district and the bodies of titaniferous magnetite that occur in a small area near the south margin of the mass have been described repeatedly, and the puzzling problems of the genesis of the rocks and ores have stimulated the deductive reasoning of geologists for a hundred years. Some of these men have taken a leading part1-15 in describing the anorthosite rock and forming hypotheses concerning its origin; some have contributed most to the study of the ore deposits;'"= and some have made classical Studies3,4,21-27 introducing a basic approach to the problems of the anorthosite rock and genesis of the titaniferous magnetites. Much of the writing on the problems of rock and ore genesis has been based on physical-chemical reasoning rather than on field and microscope observations of the rocks and ores. Most of these geologists conclude that the anorthosite was formed by true magmatic crystallization, involving previous settling or squeezing out of ferromagnesian minerals from the parent magma. The associated gabbro is a separate segregation or later intrusion, and the lighter colored and finer grained facies of the anorthosite is either a chilled border zone of the anorthosite or the result of granulation by crushing of the coarse, dark blue rock of the main mass. This blue rock, called the Marcy type, is named after the higest peak in the range. The finer grained and lighter colored rock is called the White-face, after another mountain appropriately named for a cliff colored by this facies of the anorthosite. In explaining the genesis of the ores the authors have reached no general agreement, but all consider them to be dominantly the result of magmatic processes rather than the result of replacement by pneu-matolytic or hydrothermal processes. However, in the conclusions of two authors, Osborne27 and Ste-phenson," the reader is told positively that the ore minerals were introduced after the wall rock was solid and also that the oxides are later than the silicates. This seems to mean that the ore came in as a later intrusion, like a dike, since Osborne speaks of filter pressing and later injection of a residual magma. Stephenson agrees in general with Osborne but disagrees with his conclusion that ore does not grade into country rock. Singewald22 calls in "mineralizers" to participate in magmatic deposition. Stephenson ends his paper with a statement that replacement was the dominant process for the introduction of ore with anorthosite. Hence both Singewald and Stephenson call on pneumato-lytic or hydrothermal processes to supplement magmatic crystallization from a silicate melt, but they cannot quite bring themselves to state that the orebodies formed in that way. In their conclusions the ores are still magmatic segregations and magmatic injections and—almost as an afterthought— "replacements." According to Bateman18 there was a gravitational accumulation process of the iron silicates and oxides, which were injected later. Rambere explains the ores entirely on physical-chemical theory, as does Evrard.17 Buddington and associates,10 in a paper presented to the Geological Society of America in 1953, believe the facts observed prove that the magnetite-ilmenite formed at magmatic temperatures. The present writer's conclusions, given here, were first presented in 1947 in Industrial Minerals and Rocks.= Since the papers of Ramberg, Bateman, and Buddington, published after 1947, gave no recognition to those conclusions that differ from their own, the writer has taken an opportunity to restudy the area in the field, and to examine a number of microscopic sections, and now presents the evidence more thoroughly than he had an opportunity to do in the